Respuesta :
[tex]\displaystyle\sum_{i=1}^46^{i-1}=1+6+6^2+6^3[/tex]
[tex]\displaystyle6\sum_{i=1}^46^{i-1}=6+6^2+6^3+6^4[/tex]
[tex]\implies\displaystyle\sum_{i=1}^46^{i-1}-6\sum_{i=1}^46^{i-1}=1-6^4[/tex]
[tex]\implies\displaystyle-5\sum_{i=1}^46^{i-1}=1-6^4[/tex]
[tex]\implies\displaystyle\sum_{i=1}^46^{i-1}=\dfrac{6^4-1}5=259[/tex]
[tex]\displaystyle6\sum_{i=1}^46^{i-1}=6+6^2+6^3+6^4[/tex]
[tex]\implies\displaystyle\sum_{i=1}^46^{i-1}-6\sum_{i=1}^46^{i-1}=1-6^4[/tex]
[tex]\implies\displaystyle-5\sum_{i=1}^46^{i-1}=1-6^4[/tex]
[tex]\implies\displaystyle\sum_{i=1}^46^{i-1}=\dfrac{6^4-1}5=259[/tex]